Efficient Transduction of Vascular Endothelial Cells with Recombinant Adeno-Associated Virus Serotype 1 and 5 Vectors - CHEN, SIFENG (2005)
Recombinant adeno-associated virus (rAAV) has become an attractive tool for gene therapy because of its ability to transduce both dividing and nondividing cells, elicit a limited immune response, and the capacity for imparting long-term transgene expression. Previous studies have utilized rAAV serotype 2 predominantly and found that transduction of vascular cells is relatively inefficient. The purpose of the present study was to evaluate the transduction efficiency of rAAV serotypes 1 through 5 in human and rat aortic endothelial cells (HAEC and RAEC). rAAV vectors with AAV2 inverted terminal repeats containing the human α(1)-antitrypsin (hAAT) gene were transcapsidated using helper plasmids to provide viral capsids for the AAV1 through 5 serotypes. True type rAAV2 and 5 vectors encoding β-galactosidase or green fluorescence protein were also studied. Infection with rAAV1 resulted in the most efficient transduction in both HAEC and RAEC compared to other serotypes (p < 0.001) at 7 days posttransduction. Interestingly, expression was increased in cells transduced with rAAV5 to levels surpassing rAAV1 by day 14 and 21. Transduction with rAAV1 was completely inhibited by removal of sialic acid with sialidase, while heparin had no effect. These studies are the first demonstration that sialic acid residues are required for rAAV1 transduction in endothelial cells. Transduction of rat aortic segments ex vivo and in vivo demonstrated significant transgene expression in endothelial and smooth muscle cells with rAAV1 and 5 serotype vectors, in comparison to rAAV2. These results suggest the unique potential of rAAV1 and rAAV5-based vectors for vascular-targeted gene-based therapeutic strategies. OVERVIEW SUMMARY: Gene delivery to the vasculature has significant potential as a therapeutic strategy for several cardiovascular disorders including atherosclerosis, hypertension, angiogenesis, and chronic vascular rejection of transplanted organs. However, limited advances have been made in achieving successful vascular endothelial cell gene transfer. The results of the present study demonstrate the superior efficacy of recombinant adeno-associated virus (rAAV) serotype 1 and 5 vectors in comparison to the traditionally used rAAV serotype 2 in transduction of primary vascular endothelial and smooth muscle cells in vitro. Our results have identified sialic acid residues for rAAV1 transduction in endothelial cells, similar to rAAV5. Transduction of rat aortic segments demonstrated significant transgene expression in endothelial and smooth muscle cells with rAAV1 and 5 serotype vectors both ex vivo and in vivo, while rAAV2 showed no significant transduction. These results suggest significant advantages of using alternative rAAV serotypes 1 and 5 for vascular-targeted gene delivery.